PENGARUH KESADARAN, SOSIALISASI, DAN SANKSI PERPAJAKAN TERHADAP TINGKAT KEPATUHAN WAJIB PAJAK UMKM - Cynthia, Vanessa; Trisnawati, Estralita (Fakultas Ekonomi, Universitas Tarumanagara, 2024)
This research aims to determine the influence of taxpayer awareness, taxpayer knowledge, tax socialization and tax sanctions on UMKM taxpayer compliance. The sample selection technique in this study uses simple random sampling as a form of use in collecting sample data of 100 samples of UMKM in Tangerang City. The data processing technique used in this study was assisted using Soft'sware IBM SPSS Statistics 25 generated through multiple regression analysis as a determinant in generating data in this study. The results of this study indicate that taxpayer awareness, tax socialization, and tax sanctions affect taxpayer compliance. Meanwhile, taxpayer knowledge does not affect taxpayer compliance. This research implies that there are benefits such as adding insight and learning for readers about UMKM taxes. as a capital city taxpayer, increase knowledge so that they can get to know taxation better. the better in knowing, the higher the level of compliance.